Art Crossing Borders: The Internationalisation of the Art Market in the Age of Nation States, 1750-1914 (Studies in the History of Collecting & Art Markets, 2019)
Art Crossing Borders offers a thought-provoking analysis of the internationalisation of the art market in the long nineteenth century and its unexpected and ambiguous relation with the simultaneous rise of nationalist modes of thinking. Readership: All interested in the historical and contemporary Western art markets and material culture.